2022
DOI: 10.3390/pharmaceutics14010159
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Fused Deposition Modeling and Inkjet Printing to Produce Drug Loaded 3D Printed Tablets

Abstract: In the current study, we have coupled Fused Deposition Modelling (FDM) for the fabrication of plain polyvinyl alcohol (PVA) tablets followed by dispensing of minoxidil ethanolic solutions using inkjet printing. The use of a drop-on-solid printing approach facilitates an accurate and reproducible process while it controls the deposition of the drug amounts. For the purpose of the study, the effect of the solvent was investigated and minoxidil ink solutions of ethanol 70% v/v (P70) or absolute ethanol (P100) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Additionally, a 2D approach using IJP of minoxidil ethanolic solutions onto predeveloped PVA tablets by FDM was studied, resulting in tablets with sustained release profiles or initial bursts, depending on the solvent grade (e.g., 70% v/v or absolute ethanol) used in the formulation of the pharma‐ink (Figure 8C). [ 57 ]…”
Section: Inkjet‐printed Drug Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a 2D approach using IJP of minoxidil ethanolic solutions onto predeveloped PVA tablets by FDM was studied, resulting in tablets with sustained release profiles or initial bursts, depending on the solvent grade (e.g., 70% v/v or absolute ethanol) used in the formulation of the pharma‐ink (Figure 8C). [ 57 ]…”
Section: Inkjet‐printed Drug Productsmentioning
confidence: 99%
“…3D Printed Dosage Forms 3D printed tablets prepared using other technologies, such as fused deposition modeling (FDM), exemplify the cutting-edge approach in IJP, enabling the fabrication of customized drugloaded tablets with precise dosing. [57,128] The addition of the API using IJP following FDM 3D printing ensures that thermolabile APIs remain intact and avoid thermal degradation. [129] Similarly, this could be beneficial in the case of light-sensitive APIs, preserving their integrity following powder bed fusion [130] and vat photopolymerization processes.…”
Section: Polydimethylsiloxanementioning
confidence: 99%
See 1 more Smart Citation
“…A theoretical model was also developed to help designing complex active structures with required thermomechanical properties. Combining FDM and inkjet printing was explored by Eleftheriadis et al (2020) and Junqueira et al (2022). The authors showed that the combination of FDM and inkjet printing can improve structure personalization, reproducibility and accuracy.…”
Section: Inkjet Four-dimensional Printingmentioning
confidence: 99%
“…For example, it has been used for drug loading of microneedles for transdermal drug release [ 16 , 17 , 18 ], coating and drug loading of drug-eluting stents [ 19 ], drug loading of reservoir-based systems for oral drug delivery [ 20 , 21 , 22 ] or drug laden particles [ 23 ]. Moreover, inkjet printing enables innovative hybrid 3D printing methods for more precision in drug loading of 3D printed drug delivery systems [ 24 ] or to incorporate local drug depots [ 25 ]. In sum, inkjet printing offers much potential to push the innovation portfolio for further patient specific treatments with reduced toxicity and improved efficacy, safety and patient compliance [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%